#TITLE_ALTERNATIVE# - SURYA (NIM 10105006), ADI
This final assignment describes one problem of swarm intelligence phenomena, which is the cyclic pursuit in unicycle case. Cyclic pursuit is a problem about n agents that chase each other. Each agent has a simple task. Agent with identity i must chase the agent with identity i+1 modulo n. Cyclic Pursuit in unicycle case has an orientation constraint. With this constraint, each agent must change its orientation to change its position. This final assignment describes the equilibrium point of this cyclic pursuit system and its stability properties.